Education Management For Women Empowerment In Lampung: A Systematic Literature Review - Hafizh Taufiq Fadlur Rahman; Oki Dermawan; Muhammad Anas Maarif (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2026)
Women empowerment through education is a strategic issue in sustainable development; however, significant gender gaps remain in Lampung Province. Effective education management is key to the success of women empowerment programs. This study aims to identify and analyze the conditions, models, factors, and best practices in education management for women empowerment in Lampung through a comprehensive systematic review of existing literature. The study uses the Systematic Literature Review (SLR) method with the PRISMA approach. Literature searches were conducted in international academic databases (Scopus, Web of Science, ERIC, Google Scholar) and national databases (Garuda, institutional repositories) for the period 2010-2026. The review identifies four main models of education management for women empowerment: (1) Community-Based Model with a participatory approach, (2) Multi-Stakeholder Partnership Model involving government-NGOs-community, (3) Result-Based Model with a strong M&E system, and (4) Participatory-Transformative Model focusing on women’s agency. Key supporting factors include responsive program design, transformational leadership, policy support, and social capital. Major barriers include restrictive gender norms, women’s double burden, limited resources, and weak stakeholder coordination. Effective programs lead to positive outcomes at the individual level (increased knowledge, skills, and self-efficacy), family level (increased income and children’s education), and community level (strengthened women’s organizations and changing social norms). Effective education management for women empowerment requires a holistic, contextual, and participatory approach with strong multi-stakeholder coordination. Strengthening policy commitment, improving managerial capacity, a robust M&E system, and strategies to address structural-cultural barriers are essential. This study provides an integrated conceptual framework and evidence-based recommendations for improving women empowerment programs in Lampung.